BPSL1665 does not play a role in ceftazidime resistance during biofilm growth of Burkholderia pseudomallei - Eangchuan , Nongkran; Chattagul, Supaksorn; Najomtien, Priyapa; Wongratanacheewin, Surasakdi; Sermswan, Rasana (Asia-Pacific Journal of Science and Technology, 2023)
Burkholderia pseudomallei is a Gram-negative bacterium that causes melioidosis, a serious infectious disease affecting both human and animals. Ceftazidime (CAZ) is a drug of choice. However, the bacterium in biofilm form becomes resistant to CAZ with mechanisms remain unclear. B. pseudomallei BPSL1665 is orthologue with PA1877, an efflux pump gene in Pseudomonas aeruginosa that participated in biofilm-related antibiotics resistance. BPSL1665 expressed higher in biofilm form, and a universal efflux pump inhibitor, phenylalanine arginine β-napthylamide (PAβN), could increase the CAZ sensitivity of the bacterium. B. pseudomallei BPSL1665 mutant therefore was constructed and tested for CAZ and Ciprofloxacin (CIP) susceptibility. The minimal inhibitory concentration (MIC) of wild type and the mutant of planktonic against CAZ and CIP were 4 and 2 mg/mL. The Minimum Biofilm Inhibitory Concentration (MBIC) and the Minimum Biofilm Eradication Concentration (MBEC) against CAZ of wild type and the mutant were 32 and >1024 mg/mL. The MBIC and MBEC against CIP of the wild type and the mutant were 16 and 512, and 8 and 512 mg/mL. When 50 mg/mL of PAβN was combined with each antibiotic, the titer of MBIC was reduced to 2 mg/mL, however, the MBEC against CAZ did not change. For CIP, the MBIC and the MBEC were not changed. Nevertheless, the BPSL1665 mutant showed all responses similar to its wild type. Recently, BPSL1665 has been annotated as type I secretion membrane fusion, HlyD family protein. PAβN may influence other efflux pumps that further study may help improve the B. pseudomallei biofilm treatment.